Hipoalbuminemia praoperasi pasien kanker kolorektal terhadap risiko komplikasi pascaoperasi dan lama rawat inap - Yohanes Benny; Teguh Aryandono; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2013)
Background: Malnutrition is most commonly found in gastrointestinal cancer that affects the result of an operation. Albumin serum is an effective and simple way of assessing risk which is associated with malnutrition intensity so that it is generally used as the prognostic index for the development of the incidence of colorectal cancer postoperative complications.Objective: To identify the effect of preoperative hypoalbumin to the incidence of postoperative complications and length of stay of colorectal cancer in patients.Method: The study used the quantitative approach with a nonconcurrent cohort (retrospective analysis) design. The population was patients diagnosed having colorectal cancer who would undergo an operation at Kasih Ibu, Dr. Oen, and Panti Waluyo Hospital of Surakarta. Data analysis used Chi-Square test and logistic regression.Results: Hypoalbumin, either based on admission or pre-operation, was significant risk factor for the incidence of post operative complications in colorectal cancer patients as well as age and American Society of Anesthesiologist Physical Status Classification (ASA) status. The result of multivariate analysis showed age of 20-59 years (OR=2), hypoalbumin based on admission (2.1 times) and preoperation (1.9 times) were risk factors for the incidence of postoperative complication (infection). ASA status III-IV had risk 2.8 times for the incidence of postoperative sepsis complications and 3.7 times for mortality than ASA status I-II. Status of hypoalbumin did not influence total length of stay or postoperative length of stay but age influenced postoperative length of stay.Conclusion: Hypoalbumin influenced the incidence of postoperative complications in colorectal cancer patients, particularly infection complication; whereas factors of age and ASA status were external factors strongly influenced. Hypoalbumin did not influence length of stay. Age was an external factor that strongly influenced postoperative length of stay.